Droplet spectrum generated by air induction nozzles spraying solutions containing adjuvants and a tank mixture of glyphosate and dicamba - Antuniassi, Ulisses R. [UNESP] (2020)
The aim of this work was to evaluate drift reduction technologies (DRTs) by analyzing the droplet spectrum generated by air induction nozzles spraying solutions containing adjuvants and a mixture of glyphosate and dicamba. The TTI and AIXR 11003 (Teejet), ULD and ULD Max 12003 (Hypro), and MUG 11003 (Magnojet) were used to spray a tank mixture of 3.0 L c.p./ha of a soluble concentrate (SL) formulation of glyphosate potassium salt with 480 g a.e./L and 2.0 L c.p./ha of an SL formulation of a dicamba diglycolamine salt (480 g a.e./L) at 3 bar and 100 L/ha. Four solutions were prepared: the herbicides alone and mixed with polymer, guar, and modified seed oil adjuvants. All solutions with adjuvants also received 0.5% v/v of a volatility reduction adjuvant. A factorial experiment (four solutions × five nozzles) was set up with three replications. The droplet spectrum was analyzed by the volume median diameter (VMD), the percentage by volume of droplets smaller than 150:m (V150), and the relative span using particle/droplet image analysis. There were significant interactions between nozzles and solutions for all experiments. The AIXR and ULD showed to be less advisable DRTs for dicamba plus glyphosate because they provided smaller VMD and higher V150 values. The interactions of the MUG and ULDM with the polymer adjuvant delivered droplets around 1,000:m, so its use must be discussed according to the weed species and spray volume. Guar and polymer adjuvants produced higher values of VMD and lower values of V150 for most nozzles and were good DRTs for glyphosate plus dicamba. The TTI presented a good balance between VMD and V150 for all solutions and was a robust DRT for the herbicides.